Toxicity Assessment of Brominated Haloacetic Acids - Grundy, Polly; Jarvis, Peter; Bull, Sarah (Cranfield University, 2025)
A toxicological evaluation was undertaken to identify the most sensitive point of departure (PoD) for each brominated haloacetic acid, which was then used to determine a health-based guidance value (HBGV), from which a drinking water guideline value (GV) was derived.
Report from Tara Consulting is provided.
Keywords: Brominated Disinfection By-Products; DBPs; Toxicity; Haloacetic acids; HAAs